Morphological assessment of Sargassum (Fucales, Phaeophyceae) species in Eastern Samar, Philippines - Pontica, Mark Angelo B.; Yap-Dejeto, Leni G. (2015)
A morphological assessment was conducted to describe the Sargassum species in the province of Eastern Samar, Philippines. Samples were collected from nine municipalities of Eastern Samar from February to April 2015. These were preserved in 4% formalin-seawater solution, dried, pressed and stored in University of the Philippines-Tacloban College herbarium. Gross morphological characteristics of the species such as the type of holdfast, shape and nature of its branches, vesicles, leaves, nature and distribution of cryptostomata, and nature and form of receptacle were used to discriminate the different morphotypes. Thirteen species were identified and its morphological characteristics were assessed. Out of the thirteen species, the following are of first record in Eastern Samar, Philippines up to date: S. baccularia, S. binderi, S. Cinereum, S. hemiphyllum, S. henslowianum, S. incisifolium, S. kuetzingii, S. longifructum, S. parvivesiculosum, and S. tenerrimum. Ten measurable morphological parameters and ten categorical morphological parameters of each species were assessed. The ANOVA test performed among each species showed significant difference (p<0.01) for all quantitative characters used. Agglomerative Nesting and Neihbour Joining using these characteristics showed two monophyletic clades. S. hemiphyllum turned out to be an outlier of the two lades clades.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.
Keywords: Sargassum species -- Eastern Samar, Philippines; Science and Technology